2021
DOI: 10.1017/ice.2020.1404
|View full text |Cite
|
Sign up to set email alerts
|

Virtual infection prevention—The next frontier

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has resulted in the acceleration of telehealth and remote environments as stakeholders and healthcare systems respond to the threat of this disease. How can infectious diseases and healthcare epidemiology expertise be adapted to support safe care for all?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Simultaneously, in a recent article "Virtual Infection Prevention-The Next Frontier," K. Barrows pointed out, "Healthcare trends in physician compensation, market consolidation and private equity have contributed to [a] shortage of infectious diseases specialty support." 3,4 Additionally, the Association of American Medical Colleges projects a shortage of 3,800-13,400 physicians in nonprimary-care medical specialties by 2034, while the US population ages and increases demand. 5 Staffing levels correspond to mental fatigue in nursing teams, and a recent meta-analysis reported that frontline healthcare workers are at higher risk for mental health issues related to the global crisis including posttraumatic stress disorder, anxiety, depression, and sleep disorders.…”
Section: Mounting Pressure On Infectious Diseases Expertsmentioning
confidence: 99%
“…Simultaneously, in a recent article "Virtual Infection Prevention-The Next Frontier," K. Barrows pointed out, "Healthcare trends in physician compensation, market consolidation and private equity have contributed to [a] shortage of infectious diseases specialty support." 3,4 Additionally, the Association of American Medical Colleges projects a shortage of 3,800-13,400 physicians in nonprimary-care medical specialties by 2034, while the US population ages and increases demand. 5 Staffing levels correspond to mental fatigue in nursing teams, and a recent meta-analysis reported that frontline healthcare workers are at higher risk for mental health issues related to the global crisis including posttraumatic stress disorder, anxiety, depression, and sleep disorders.…”
Section: Mounting Pressure On Infectious Diseases Expertsmentioning
confidence: 99%
“…102,103 Recognising that much of health care is delivered in environments without experts in infectious diseases, antimicrobial stewardship, micro biology, and infection prevention, virtual infection pre vention platforms could be leveraged to assist rural environments and lowresource settings through real-time, expert consultation. 104 Successful models exist for the community expansion of health-care epidemiology programmes. 105 In the innovative and expansive spirit of Pasteur, the collaborative effort engaged through the One Health approach might minimise excessive anti microbial consumption, and preserve agents for looming threats.…”
Section: Future Challenges To Infection Controlmentioning
confidence: 99%